Universitas Gadjah Mada dalam Pusaran Konflik 1965 - Willy Alfarius (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta, 2022)
This article discusses the impact of the September 30 Movement (G30S) 1965 incident on Gadjah Mada University (UGM) in Yogyakarta. Exactly, this research takes a temporal limitation since it happened in early October 1965 until 1968 when the national political transition period can be said to have ended. In particular, this research outlines the university's response to the incident and the reasons for taking campus action against students and lecturers who were accused of being involved, either directly or indirectly. In addition, it also discussed the conditions of campus life in a socio-political situation which was full of tension, as well as the direction of campus policies after the socio-political situation which had begun to stabilize thereafter.This research uses the historical method, which begins by choosing a theme, then continues by looking for contemporaneous sources, especially newspapers such as Nasional, Mertju Suar, Suluh Marhaen, to UGM's internal archives. After verification and interpretation of the sources found, reconstruction and writing were carried out, mainly based on the various research questions above.From the results of the research, it was found that thousands of students, along with several UGM lecturers and staff, were temporarily dismissed from the campus because of their affiliation with various organizations that were considered to be wings of the PKI. Most of them were later declared fired, while a handful of them were reinstated. They were considered part of organizations which the government under Suharto's control were considered banned because they were accused of being involved in the G30S 1965 Incident. Not only were there dismissals and turmoil on campus. Along with the change in political direction at that time, UGM's orientation also changed according to the tendencies of the new government after the dismissal of Sukarno as president. Tulisan ini membahas mengenai dampak Peristiwa Gerakan 30 September (G30S) 1965 terhadap Universitas Gadjah Mada (UGM) di Yogyakarta. Persisnya penelitian ini mengambil batasan temporal dari awal Oktober 1965 hingga tahun 1968 ketika masa transisi politik nasional dapat disebut selesai. Terutama sekali penelitian ini menguraikan respons universitas terhadap adanya peristiwa tersebut serta sebab-sebab yang menjadi alasan bagi diambilnya tindakan kampus terhadap mahasiswa dan dosen yang dituduh terlibat, baik secara langsung maupun tidak langsung. Selain itu, dibahas pula kondisi kehidupan kampus dalam suasana sosial-politik yang penuh ketegangan, serta arah kebijakan kampus pasca situasi sosial-politik yang sudah mulai stabil setelahnya.Penelitian ini menggunakan metode sejarah, yang dimulai dengan memilih tema, kemudian dilanjutkan dengan mencari sumber-sumber sezaman, terutama surat kabar seperti Nasional, Mertju Suar, Suluh Marhaen, hingga arsip-arsip internal UGM. Setelah dilakukan verifikasi serta interpretasi terhadap sumber-sumber yang ditemukan, maka dilakukan rekonstruksi dan penulisan, terutama didasarkan atas berbagai pertanyaan penelitian di atas.Dari hasil penelitian, ditemukan fakta bahwa ribuan mahasiswa, bersama beberapa dosen serta pegawai UGM diberhentikan sementara dari kampus oleh karena afiliasinya dengan berbagai organisasi yang dianggap sebagai sayap PKI. Sebagian besar dari mereka kemudian dinyatakan dipecat, sedangkan segelintir dari mereka ada yang dipulihkan kembali statusnya. Mereka dianggap sebagai bagian dari organisasi-organisasi, yang oleh pemerintah berwatak militer di bawah kendali Suharto, dianggap terlarang karena dituduh terlibat dalam Peristiwa G30S 1965. Tidak hanya terjadi pemecatan dan gejolak di dalam kampus, seiring dengan berubahnya haluan politik saat itu, orientasi UGM juga ikut berubah menyesuaikan dengan kecenderungan pemerintahan yang baru pasca diberhentikannya Sukarno sebagai presiden.